2020
DOI: 10.3390/s20051252
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Oxide-Based Electrochemical Sensors for the Sensitive Detection of Pharmaceutical Drug Naproxen

Abstract: Here we report on a selective and sensitive graphene-oxide-based electrochemical sensor for the detection of naproxen. The effects of doping and oxygen content of various graphene oxide (GO)-based nanomaterials on their respective electrochemical behaviors were investigated and rationalized. The synthesized GO and GO-based nanomaterials were characterized using a field-emission scanning electron microscope, while the associated amounts of the dopant heteroatoms and oxygen were quantified using x-ray photoelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 42 publications
2
34
0
1
Order By: Relevance
“…Nowadays, analytical techniques used for drug analysis, food analysis, environment, and health include nanomaterials as the main constituent as nanomaterials can improve the interaction with analyte due to their exceptional electronic, chemical, physical properties as well as their high surface area [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Several factors affect the efficiency of nanomaterials-based sensors such as dimensions, morphology, crystallographic axis orientation, crystal structure quality, and chemical composition that determine the rate of electron transfer and degree of interaction [ 21 ]. Thus, clinical and analytical instruments used nanomaterials for sensing purposes due to their exceptional potential.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, analytical techniques used for drug analysis, food analysis, environment, and health include nanomaterials as the main constituent as nanomaterials can improve the interaction with analyte due to their exceptional electronic, chemical, physical properties as well as their high surface area [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Several factors affect the efficiency of nanomaterials-based sensors such as dimensions, morphology, crystallographic axis orientation, crystal structure quality, and chemical composition that determine the rate of electron transfer and degree of interaction [ 21 ]. Thus, clinical and analytical instruments used nanomaterials for sensing purposes due to their exceptional potential.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical techniques have then become popular for detecting very small amounts of molecules that could be either oxidizing or reducing agents. The relatively low costs and simple measurement procedures, requiring a three-electrode system and a potentiostat to scan for the redox potentials that return the signal of molecules, led to the possibility of developing the portable sensing platforms [17][18][19]. Many studies showed that using a cyclic voltammetry (CV) or differential pulse voltammetry (DPV) with glassy carbon electrodes (GCE) can detect AA, DA, and UA up to the micromolar limit of detection [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical techniques have then become popular for detecting very small amounts of molecules that could be either oxidizing or reducing agents. The relatively low costs and simple measurement procedures, requiring a three-electrode system and a potentiostat to scan for the redox potentials that return the signal of molecules, led to the possibility of developing the portable sensing platforms [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the disadvantages of these methods for clinical use are the high cost and complicated procedures [17][18][19][20][21][22][23][24]. To overcome these issues, electrochemical techniques are used for detecting very small amounts of molecules and have become popular due to their low costs and relatively simple procedures [25][26][27][28][29]. Many studies showed that using a cyclic voltammetry (CV) or differential pulse voltammetry (DPV) with glassy carbon electrodes (GCE) can detect AA, DA, and UA up to the micromolar limit of detection [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%